1980
DOI: 10.1111/j.1600-0773.1980.tb01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose Pharmacokinetics of Doxepin in Healthy Volunteers

Abstract: Abstraci:The pharmacokinetics of orally administered doxepin (50 mg) was studied in 8 healthy volunteers. Doxepin (DOX) and desmethyldoxepin (DDOX) concentrations in serum (or plasma) and red blood cells (RBCs) were measured by radioimmunoassay. Peak serum concentrations of DOX were observed at 1-2 hours and they ranged between 59.1-107.4 nmol/l. DOX disappearance was biphasic with a mean distribution halflife of 2.0 hrs and elimination half-life of 17.9 hrs. The mean total apparent volume of distribution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Assuming linear kinetics, the C max expected for a single 150 mg dose of amitriptyline is 0.45 mM. Doxepin (50 mg dose): mean C max 0.29 mM (Virtanen et al, 1980), fu 0.79 (Faulkner et al, 1983). Again, assuming linear kinetics, the C max expected for a single 150 mg dose of doxepin is 0.87 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming linear kinetics, the C max expected for a single 150 mg dose of amitriptyline is 0.45 mM. Doxepin (50 mg dose): mean C max 0.29 mM (Virtanen et al, 1980), fu 0.79 (Faulkner et al, 1983). Again, assuming linear kinetics, the C max expected for a single 150 mg dose of doxepin is 0.87 mM.…”
Section: Methodsmentioning
confidence: 99%
“…16 Single dose studies have indicated sedative effects lasting up to 5 h, 17 consistent with the reported half-life of racemic dimethindene (∼5 h). 18 More recently, doxepin, a potent antihistamine with elimination half-life of 18 h, 19 has shown sleep maintenance effects lasting up to 8 h at low doses with no next day residual effects. 15 While 1a exhibited less than ideal duration of action for the treatment of insomnia, the compound represented an excellent starting point to identify novel analogues for clinical evaluation that retained receptor selectivity with potentially improved pharmacokinetic profile.…”
mentioning
confidence: 99%